Advanced molecular tools for surveillance and management of tobamoviruses - Mehmood, Mirza Abid; Iqbal, Muhammad Mazhar; Ashfaq, Muhammad; Chen, Suiyun; Wang, Jianguang (Frontiers in Plant Science, 2026)
Tobamoviruses are a group of plant viruses that can cause yield losses of up to 70% and reduce fruit quality by 30–50%. Historically, tobamoviruses were dominated by tobacco mosaic virus (TMV) and tomato mosaic virus (ToMV). However, the landscape is rapidly shifting with the emergence of economically significant viruses such as tomato mottle mosaic virus (ToMMV) and tomato brown rugose fruit virus (ToBRFV). Both can circumvent the previously durable Tm-2² resistance in tomato and spread across multiple continents. This shift coincides with dramatic leaps in diagnostic tools, which have enhanced surveillance capabilities. Sensitive detection of tobamoviruses in the field with minimal sample preparation can be achieved using latest technologies such as isothermal amplification, CRISPR/Cas-hybrid assays or next-generation sequencing. Virus-host interactions underscore that viral proteins, including replicase components, are potent suppressors of RNA silencing (VSRs). Small RNA profiling and network analyses of viral movement proteins reveal complex mechanisms of immune evasion and resistance breakdown. These findings are largely based on dominant NB-LRR genes such as L, Tm-1, and Tm-22. However, evidence indicates that ToBRFV can bypass this resistance via mutation in the movement protein, so supplementary methods should be considered. This review covers latest approaches, such as genome editing with CRISPR, targeting susceptibility genes, RNA interference (RNAi), and multi-omics approaches (transcriptomics, proteomics, metabolomics, ionomics), that can facilitate real-time surveillance and breeding for enhanced resilience. Moreover, the use of bio-formulations and nano-formulations as eco-friendly alternatives against tobamoviruses is discussed in detail. Climate change further complicates disease dynamics by undermining temperature-sensitive resistance, altering virus prevalence, and exacerbating yield losses. The rapid emergence of new tobamoviruses, which threatens the economy, necessitates a comprehensive approach. The integration of molecular diagnostics using CRISPR, omics technologies, designed protective systems, and climate-augmented disease prediction offers a detailed blueprint for the sustainable control of tobamoviruses and crop protection.